Breaking Continuous Flash Suppression: A New Measure of Unconscious Processing during Interocular Suppression? - Stein, Timo; Hebart, Martin N.; Sterzer, Philipp (Frontiers in Human Neuroscience, 2011)
Until recently, it has been thought that under interocular suppression high-level visual processing is strongly inhibited if not abolished. With the development of continuous flash suppression (CFS), a variant of binocular rivalry, this notion has now been challenged by a number of reports showing that even high-level aspects of visual stimuli, such as familiarity, affect the time stimuli need to overcome CFS and emerge into awareness. In this “breaking CFS” (b-CFS) paradigm, differential unconscious processing during suppression is inferred when (a) speeded detection responses to initially invisible stimuli differ, and (b) no comparable differences are found in non-rivalrous control conditions supposed to measure general threshold differences between stimuli. To critically evaluate these assumptions was the aim of the present study. In six experiments we compared the time upright and inverted faces needed to be detected. We found that not only under CFS, but also in control conditions upright faces were detected faster and more accurately than inverted faces, although the effect was larger during CFS. However, reaction time (RT) distributions indicated critical differences between the CFS and the control condition. When RT distributions were matched, similar effect sizes were obtained in both conditions. Moreover, subjective ratings revealed that CFS and control conditions are not perceptually comparable. These findings cast doubt on the usefulness of non-rivalrous control conditions to rule out mere detection threshold differences as a cause of shorter detection latencies during CFS. In conclusion, we acknowledge that the b-CFS paradigm can be fruitfully applied as a highly sensitive device to probe differences between stimuli in their potency to gain access to awareness. However, our current findings suggest that such differences can not unequivocally be attributed to differential unconscious processing under interocular suppression.